Administrative Burden: Untangling a Bowl of Conceptual Spaghetti. Issue 1 (24th December 2021) - Baekgaard, Martin; Tankink, Tara
Abstract: Administrative burdens in citizen-state interactions are increasingly gaining attention in both research and practice. However, being a relatively young research field, there is still considerable disagreement about how to conceptualize and measure administrative burdens. In particular, burdens are sometimes equated with what the state does, and other times with what target group members experience. We argue that such disagreement is a barrier for further theoretical development and has removed focus from studying the process in which state actions are converted into individual outcomes. We provide advice on how to conceptually bridge the gap between different conceptualizations of administrative burden and lay out a research agenda covering the next important theoretical and empirical steps based on such a shared understanding. We propose that developing the conceptual and empirical foundation of administrative burden research will help asking new and important research questions and building cumulative knowledge. To illustrate these points, we present a series of new research questions for future research to engage with.